Impaired VEGF Signaling in Lungs with Hypoplastic Esophageal Atresia and Effects on Branching Morphogenesis - Xiaomei Liu; Caixia Liu; Tie Ma; Yisheng Jiao; Jianing Miao; Linlin Gao (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Patients with esophageal atresia (EA) and tracheoesophageal fistula (TEF) often suffer chronic respiratory tract disease. We previously reported that primary lung maldevelopment caused by deficient branching of embryonal airways in experimental EA-TEF was induced by Adriamycin. In this study, we investigated the Vascular endothelial growth factor (VEGF) pathway in the developing lung in an EA-TEF rat model. We further analyzed the effect of recombinant VEGF treatment in vitro on branching morphogenesis of embryo lungs in experimental EA-TEF. Methods: Pregnant rats received either Adriamycin or vehicle on E7, E8 and E9. Lungs were recovered at E15, E18 and E21. Expression of VEGF and receptors (Flk-1 and Flt-1) were assessed by quantitative PCR, immunohistochemistry and immunoblotting. E13 lungs were cultured for 72 hours with 50 ng/mL of recombinant rat VEGF in serum-free medium. The rates of increase in bud count and airway contour were evaluated. Results: Our results showed a significant downregulation of VEGF during pseudoglandular and canalicular stages. In contrast, there were significantly higher levels of the Flt-1 receptor in the canalicular stage, which may represent a compensatory response to decreased VEGF. However, both variables returned to normal levels at the saccular stage. Exogenous VEGF treatment enhanced hypoplastic lung growth, evidenced by the increase in bud count and airway contour. Conclusions: A VEGF signaling defect possibly plays an important role in defective embryonic airway branching. Additionally, VEGF treatment may accelerate lung growth in EA-TEF lungs.